Implementasi Biology Club I di SMA Karitas Watuneso, Kecamatan Lio Timur, Kabupaten Ende - Bare, Yohanes; Putra, Sukarman Hadi Jaya; Bunga, Yohanes Nong; Mago, Oktavius Yoseph Tuta; S, Mansur; Tematan, Yohanes Boli (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Biology learning is defined as material that is difficult to experience biological concepts. The biology learning offered must have a role as something easy to implement. The collaboration of games and biology is one of the concepts to introduce biology that plays a game. Therefore, my Biology Club Team took the initiative to provide experiences and emphasize the deep character of biology to motivate students. This research aims to integrate biology material and games at Karitas Watuneso High School in Biology Club I activities. We collaborated direct instruction, demonstration, and discussion methods. The implementation of Biology Club I at Karitas Watuneso High School received a positive response with the highest level of satisfaction starting from the Zoology Games, Botany Games, and Microbiology Games. The level of significance of Biology Club I received the highest score, followed by material understanding and activity satisfaction.